2016
DOI: 10.1111/ffe.12481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high speed on crack propagation path in thin rim gears

Abstract: A B S T R A C T Thin rim gears need accurate design as cracks nucleated at the tooth root fillet may propagate in a safe way (through the tooth) or in catastrophic way (through the rim). Crack propagation direction is mainly influenced by both wheel geometry parameters and crack initiation point. For specific geometry configurations, crack propagation path may be influenced also by other parameters such as the centrifugal load. For this reason, in this work the effect of the centrifugal load (proportional to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…On the basis of previous simulations results [1][2][3], it was noted that the crack propagation direction was mainly influenced by both wheel geometry parameters and crack initiation point. Results related to gear models with different web and rim thicknesses were also interpreted in ISO Standard environment [4], relating the crack path to the so called gear blank factor CR, useful in cases of mating gears consisting of rims and webs.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the basis of previous simulations results [1][2][3], it was noted that the crack propagation direction was mainly influenced by both wheel geometry parameters and crack initiation point. Results related to gear models with different web and rim thicknesses were also interpreted in ISO Standard environment [4], relating the crack path to the so called gear blank factor CR, useful in cases of mating gears consisting of rims and webs.…”
Section: Introductionmentioning
confidence: 91%
“…Results related to gear models with different web and rim thicknesses were also interpreted in ISO Standard environment [4], relating the crack path to the so called gear blank factor CR, useful in cases of mating gears consisting of rims and webs. Results showed that the interaction between web and rim thickness may influence the crack propagation and the corresponding safe or catastrophic failure mode [1][2][3], [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The XFEM was successfully adopted to gears to observe fatigue crack propagation. 4,5,14 In this study, the XFEM was utilized to understand the role of prestressing caused by interference in fatigue crack growth in a spur gear.…”
Section: Introductionmentioning
confidence: 99%
“…6 Lightweight gears are mainly studied in the literature about what concerns fatigue strength, crack propagation and gear dynamics. As some examples, Lewicki and Ballarini 7 and Lewicki 8 and Cura`et al 9 investigated the crack path behaviour in thin rim gears. Other works are more related to the fatigue life estimation such as Kramberger et al 10 who investigated the effect of rim thickness on bending fatigue life of a thin rim gear for truck gearbox.…”
Section: Introductionmentioning
confidence: 99%
“…As some examples, Lewicki and Ballarini 7 and Lewicki 8 and Curà et al. 9 investigated the crack path behaviour in thin rim gears. Other works are more related to the fatigue life estimation such as Kramberger et al.…”
Section: Introductionmentioning
confidence: 99%